Public investment quality and its implications for sovereign risk and debt sustainability - Amat Adarov; Ugo Panizza (Graduate Institute of International and Development Studies, 2024)
This paper introduces a novel index to measure public investment quality, utilizing the World Bank's investment project performance data from 120 countries over the period 2000-2021. After detailing the construction of the index, the paper examines how public investment quality influences the relationship between the level of public investment and sovereign risk. We find that high levels of public investment are linked to lower sovereign risk in countries with high investment quality, and conversely, to higher sovereign risk in countries with low investment quality. This relationship is especially pronounced in sub-investment grade countries. We corroborate these results by showing that when public investment quality is high, scaling up public investment enhances fiscal sustainability by reducing the debt-to-GDP ratio in the long run: highquality public investment is self-financing. However, the opposite is true when public investment quality is low, where increased public investment results in a deterioration of fiscal fundamentals.
Keywords: E22; G24; H54; H63; 330; Public investment; Public investment quality; Sovereign risk; Debt sustainability